1981
DOI: 10.1007/bf00254512
|View full text |Cite
|
Sign up to set email alerts
|

Lateral hypothalamic control of metabolic factors related to feeding

Abstract: Summary.States of hunger and satiety are under ischymetric (i. e., rate of cellular energy production) control which depends on both substrate availability and hormonal composition. The latter varies in response to external (olfactory, gustatory and gastrointestinal) stimuli sensed by specific receptors and projected on lateral hypothalamic (LH) units from which departs the descendant control pathway of metabolic glands. This neurohormonal loop is responsible for the anticipatory glycemic and other changes obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 40 publications
(11 reference statements)
2
11
0
Order By: Relevance
“…These data suggest that taste activity may vary between states of hunger and satiety. Because the LH is involved in both feeding behavior and metabolic homeostasis (Grossman and Grossman 1982;Nicolaidis 1981) and reciprocally connected to both pontine and medullary taste nuclei (van der Kooy et al 1984;Whitehead et al 2000), it is in a position to influence gustatory afferent activity. LH stimulation induces feeding FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that taste activity may vary between states of hunger and satiety. Because the LH is involved in both feeding behavior and metabolic homeostasis (Grossman and Grossman 1982;Nicolaidis 1981) and reciprocally connected to both pontine and medullary taste nuclei (van der Kooy et al 1984;Whitehead et al 2000), it is in a position to influence gustatory afferent activity. LH stimulation induces feeding FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although LP lipase activity decreased in all brain regions, the largest decrease occurred in hypothalamic LP lipase. LP lipase-dependent fatty acid uptake into brain cells in the hypothalamus is particularly noteworthy because food intake and body weight are to a large extent regulated in this brain region (13,14). Lesions in the ventromedial nucleus of the hypothalamus in rats result in increased food intake and weight gain (15); similar lesions in the lateral hypothalamus variably cause decreases in food intake and weight loss (15,16).…”
Section: Exposure Of Cultured Brain Cells To Emulsified [14c]trioleinmentioning
confidence: 99%
“…Indeed, the leastcarbohydrate-rich bread (number of slices and proportion) was consumed after the sweetest carbohydrate breakfast (HC), which induced the highest EE;,the amount of carbohydrate-rich bread consumed during the snack correlated negatively with EE; and multiple linear regressions showed that the amount of carbohydrate-rich bread consumed was related only to EE. The influence of EE on food intake has been observed in rats, leading to the ischymetric hypothesis, which suggests that feeding is controlled by the intensity of metabolic rate (35,36). According to this hypothesis, a rise in the total oxidation rate results in a decrease in food intake and vice versa (8,37).…”
Section: Wanting and Eementioning
confidence: 99%